Cerebral Computed Tomography-Graded White Matter Lesions Are Associated With Worse Outcome After Thrombolysis in Patients With Stroke. Issue 6 (June 2015) - Curtze, Sami; Melkas, Susanna; Sibolt, Gerli; Haapaniemi, Elena; Mustanoja, Satu; Putaala, Jukka; Sairanen, Tiina; Tiainen, Marjaana; Tatlisumak, Turgut; Strbian, Daniel
Abstract : Background and Purpose—: Compared with other stroke causes, small-vessel disease is associated with better 3-month outcomes in patients with acute ischemic stroke treated with intravenous thrombolysis. Another question is the impact of coexisting cerebral white matter lesions (WMLs; a surrogate marker of small-vessel disease) on outcome, which was addressed in the current study. Methods—: We analyzed 2485 consecutive intravenous thrombolysis–treated patients at the Helsinki University Central Hospital, 2001 to 2014. WMLs were scored according to 4 previously published computed tomographic visual rating scales from all baseline head scans. The inter-rater agreement was calculated. The primary outcome measure was shift analysis, and the secondary examined all possible binary cutoffs in the modified Rankin Scale at 3 months. The associations of modified Rankin Scale with nominal, ordinal, and continuous variables were analyzed in univariate and adjusted in multivariate binary and ordinal regression (shift analysis) models. Results—: In univariate and multivariate regression analyses, all 4 tested visual WML rating scales (as continuous variables, or dichotomized at different cutoff points) were associated with worse outcome at all binary levels and in shift analyses of the modified Rankin Scale. After adjusting for confounders, the statistically strongest association in shift analyses remained for the Blennow scale dichotomized at >3 points, reflecting at least moderate WMLs (odds ratio, 1.90; 95% confidence interval, 1.48–2.44). Conclusions—: WMLs on admission computed tomographic scan are independently associated with worse outcome in intravenous thrombolysis–treated patients with stroke. Abstract : Supplemental Digital Content is available in the text.